PERTUMBUHAN VEGETATIF DAN PRODUKTIVITAS BERBAGAI KULTIVAR BROKOLI (Brassica oleracea L. var. italica Plenck.) INTRODUKSI DI DESA BATUR, KECAMATAN KINTAMANI, KABUPATEN BANGLI, BALI - Raleni, Ni Kadek; Defiani, Made Ria; Astarini, Ida Ayu (Metamorfosa: Journal of Biological Sciences; Vol 2 No 2 (2015), 2015)
Broccoli ( Brassica oleracea L. var. italica Plenck .) is a vegetable crop belongs to Brassicaceae family.  Broccoli has high nutrition, high in fiber and contains isotiacyanate that has anticancer activity.  Broccoli market in Indonesia, particularly in modern supermarkets, increases 15-20% per year, however, productivity was still low, therefore effort to increase broccoli production in Indonesia need to be investigated. Field trial was conducted at Batur Village, Kintamani District, Bangli Regency, Bali, to find out cultivars that were adapted in tropical region. Introduced cultivars being trialed were ‘ Alborada’, ‘Belstar’, ‘Fiesta’ , ‘Sarasota’ , ‘Bay Meadows’, ‘Castle Dome’ , ‘Liutenant’ , ‘Iron Man’ , ‘Marathon’ , ‘Green Gold’ , ‘Imperial’ , ‘Green Magic’ and ‘ Lucky’ as control.  Variable observed were vegetative growth, curding period, and productivity of each cultivar.  This study employed Randomized Completely Block Design with 3 replicates (plots) and 8 plants each plot.  Data were analyzed using ANOVA (Analysis of variance) on Costat program, followed by Duncan’s Multiple Range Test (DMRT) on 1% level.  Results show that each cultivar varied in adaptability in tropical region. ‘Castle Dome’ has the highest productivity, while ‘Fiesta’ was the lowest. Keywords: Brassica, field trial, cultivar
Keywords: Brassica, field trial, cultivar